زكاة الأسهم و شركات المساهمة - بالي, عبد الحميد (University of Eloued جامعة الوادي, 2014)
قَبِل الفقه الإسلامي الشخصية الاعتبارية للشركة من حيث المبدأ؛ لكنه لا يقرّ جميع ما منحها القانون من صلاحيات، فلا تنتقل ملكية موجودات الشركة إلى إدارة الشركة في التكييف الشرعي للأسهم، وإذا أرادت الشركة أن تخرج الزكاة، فإنها تعامل معاملة الشخص الطبيعي من حيث النصاب والحول ونشاط الشركة، أما إذا أخرجها المساهم فإن مدار كيفية زكاته على قصده من تملك الأسهم، فإن كان قصده الاستثمار زكّى بحسب نشاط الشركة، وإن كان قصده المتاجرة زكى بالقيمة السوقية للسهم. Islamic jurisprudence admits artificial personality of the company in principle, But it does not recognize all authorities granted to it by the law. In light of the legitimate adaptation of shares, the ownership of the assets of the company are not transmitted to the company's management. If the company wants to pay Zakat, they will be treated as a natural person in terms of Nisaab, Haoul and the company's activity. If the shareholder wants to pay Zakat, the payment of zakat is based on the intention to own shares. If his intent is to invest, it pays Zakat according to the company's activity. If his intent is to trade, it pays Zakat according to the market value of shares.
مقال بمجلة البحوث والدراسات
Keywords: الزكاة- الأسهم- شركات المساهمة- الزكاة المعاصرة; Zakat - shares - stock companies - Contemporary Zakat